2016
DOI: 10.1128/aac.00518-16
|View full text |Cite
|
Sign up to set email alerts
|

Development of an In Vitro Assay for Detection of Drug-Induced Resuscitation-Promoting-Factor-Dependent Mycobacteria

Abstract: Tuberculosis is a major infectious disease that requires prolonged chemotherapy with a combination of four drugs. Here we present data suggesting that treatment of Mycobacterium tuberculosis, the causative agent of tuberculosis, and Mycobacterium smegmatis, a model organism widely used for the screening of antituberculosis agents, with first-line drugs resulted in the generation of substantial populations that could be recovered only by the addition of a culture supernatant from growing mycobacteria. These bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 29 publications
6
23
1
Order By: Relevance
“…Other reported in vitro models for producing DD Mtb include hypoxia and starvation with antibiotic exposure (19), potassium depletion (41), exposure of log-phase cells to antibiotics (42), and gradual acidification (43). It is not clear why we did not succeed in producing DD Mtb with methods like these.…”
Section: Discussionmentioning
confidence: 82%
“…Other reported in vitro models for producing DD Mtb include hypoxia and starvation with antibiotic exposure (19), potassium depletion (41), exposure of log-phase cells to antibiotics (42), and gradual acidification (43). It is not clear why we did not succeed in producing DD Mtb with methods like these.…”
Section: Discussionmentioning
confidence: 82%
“…While there are many outstanding questions on the precise mechanisms of PknB-mediated regulation of gene expression and Lsr2 binding to DNA, our findings provide a functional link between serine/threonine protein kinase signalling and transcriptional regulatory pathways that enable Mtb to survive the varied environments encountered during infection. Bacterial growth was measured by absorbance at 580nm, or by colony-forming unit (CFU) counting on 7H10 agar (Becton, Dickinson and Company), or by most probable number (MPN) counting using established protocols (Loraine et al, 2016) and the MPN calculator program (Jarvis et al, 2010). Escherichia coli OverExpress™ C41(DE3) and DH5α were grown in Lysogeny broth.…”
Section: Discussionmentioning
confidence: 99%
“…SMM comprised of 0.3 M sucrose, 20 mM MgSO 4 , 0.1% Tween 80 (w/v), 10% (v/v) ADC in standard 7H9 broth. Bacterial growth was measured by absorbance at 580nm, or by colony‐forming unit (CFU) counting on 7H10 agar (Becton, Dickinson and Company), or by most probable number (MPN) counting using established protocols (Loraine et al , ) and the MPN calculator program (Jarvis et al , ). Escherichia coli OverExpress™ C41(DE3) and DH5α were grown in Lysogeny broth.…”
Section: Methodsmentioning
confidence: 99%
“…Loraine et al recently showed that Rpf overexpression rescues non-culturable mycobacteria, generated by treatment with first-line antimicrobial agents in vitro . In addition, Loraine et al proved that the RpfD-overexpressing M. smegmatis strains showed consistently higher resuscitation, compared to the other Rpfs [ 24 ]. Interestingly, rpfD was the most prevalent (66.66%) and overexpressed gene in our study (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%